Vehicle crime prevention and the co-evolutionary arms race: recent offender countermoves using immobiliser bypass technology. Issue 1 (January 2017) - Brown, Rick
Abstract The history of vehicle security has been marked by a continuing co-evolutionary arms race in which improvements in security introduced by motor manufacturers are eventually defeated by offenders, leading to further improvements in vehicle security. This paper explores the use of immobiliser bypass technology that has been used in recent years to overcome electronic immobilisers, which had previously proven effective in preventing vehicle theft for a quarter of a century. A range of reasons for the offender countermove are put forward, including permissive European Commission regulation that has provided open access to vehicle electronic systems, the availability of immobiliser bypass tools and a degree of complacency among motor manufacturers which has resulted in the development of keyless ignition systems that have proven vulnerable to attack.